Strengthening Higher-Order Thinking Skills (HOTS) in Economics Education: A Systematic Review of Innovative Learning Models - Abdurrahim (Formad English Foundation NTB Jakarta, 2026)
Strengthening Higher-Order Thinking Skills (HOTS) has become a fundamental priority in twenty-first-century education and should be systematically fostered through economics education. HOTS plays a crucial role in enhancing students' critical, analytical, evaluative, and creative thinking abilities, enabling them to understand and solve complex economic problems. This study aims to analyze the development of research on strengthening HOTS in economics education, identify the innovative instructional models employed, and examine their effectiveness in enhancing students' higher-order thinking skills. The study adopted a qualitative approach using the Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The data were collected from scholarly articles published in Google Scholar, Scopus, and the Directory of Open Access Journals (DOAJ) between 2020 and 2026. A total of 30 articles that met the inclusion criteria were selected and analyzed using descriptive qualitative analysis. The findings indicate that Problem-Based Learning (PBL), Project-Based Learning (PjBL), Inquiry Learning, Case-Based Learning (CBL), Discovery Learning, and Blended Learning are effective instructional models for developing students' higher-order thinking skills. These pedagogical approaches consistently promote critical analysis, problem-solving, decision-making, and reflective thinking within authentic economic contexts. The study concludes that strengthening HOTS in economics education requires the systematic integration of innovative, student-centered instructional models to support the development of twenty-first-century competencies and to create more adaptive, contextualized, and meaningful learning experiences.